INNOVATION OF THE ASAHAN ONE DATA (ASADA) APPLICATION IN ASAHAN DISTRICT AS A RESPONSE TO THE INDONESIAN ONE DATA POLICY - Sipayung, Neelin Novita; Hardjono, Retno Kusumastuti (International Journal of Social Service and Research, 2024)
Innovation is urgently needed in human life with the aim of providing convenience and development through good ideas and thoughts. The Asahan One Data application is one of the innovations as a form of response from Asahan Regency to the One Data Indonesia (SDI) Policy. The ASADA application is a web-based application that is entered by all regional apparatus organizations in Asahan Regency. The purpose of making this application is to obtain data that can be accounted for, improve the quality of governance of the Asahan district government, and most importantly to obtain accurate data. Satu Data Indonesia is an integrated governance policy, has easy access, can be shared and accounted for to all agencies, both central and regional, with the principles of data standards, metadata, data interoperability, and by using master data and reference codes. The type of research used in this study is descriptive research. Researchers describe a symptom, event, and event that has occurred or is happening to be described as it is. In this study, five (5) factors for innovation success according to Cook, Matthews, Irwin will be used, namely leadership, organization management, risk management, human capital, and technology). Based on this research, the innovation of the Asahan Satu Data application still needs a lot of thought and development in order to have a maximum impact.